Hieracium certovicae (Asteraceae), a new species in H. sect. Alpestria from the Nízke Tatry Mts, Western Carpathians, Slovakia - Chrtek, Jindřich; Szeląg, Zbigniew (Phytotaxa, 2025)
Hieracium certovicae is a new, tetraploid (x=9) species from the subalpine zone in the Nízke Tatry Mts., Slovakia. It combines the morphological features of H. prenanthoides s.lat. and probably H. caesium s.lat., and belongs to the H. carpathicum aggregate.